"PHILOSOPHY OF RANK" IN PROJECTION OF NOVELISTICHNOGO THOUGHT OF LEONID MOSENDZ - Maftyn, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Influencing of "philosophy of rank" as determinants of "volitional nationalism" in small prose of Leonid Mosendz is analysed in the article. It is led to, that exactly "philosophy of rank" in the projection of his novelistichnogo thought gets up the dominant constituent of "ideology-price" level of composition of small prose of writer, predetermines appearance of a new genre variety – short "story of test of characters". "Philosophy of rank" determinate also the behavior model of person world of the analyzed works of Leonid Mosendz.